2005
DOI: 10.1093/fampra/cmh723
|View full text |Cite
|
Sign up to set email alerts
|

Societal perspectives on over-the-counter (OTC) medicines

Abstract: This survey revealed that the general public had a high level of awareness of the abuse potential of OTC medicines. These findings indicate that pharmacists could be more proactive in the management of inappropriate OTC drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
191
10
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(220 citation statements)
references
References 21 publications
16
191
10
3
Order By: Relevance
“…The proportion of respondents who preferred to use the same pharmacy (55%) was slightly lower than in previous studies conducted in other countries 10,18,19 and in England, where it varies, being higher in rural locations 15,20 . Our findings may be due to our sample being primarily suburban.…”
Section: Discussioncontrasting
confidence: 67%
“…The proportion of respondents who preferred to use the same pharmacy (55%) was slightly lower than in previous studies conducted in other countries 10,18,19 and in England, where it varies, being higher in rural locations 15,20 . Our findings may be due to our sample being primarily suburban.…”
Section: Discussioncontrasting
confidence: 67%
“…In our study, individuals who were dependent on non-prescription medicine use informed us that they were never asked by pharmacy staff about their motive of procurement of medicines and this observation is in concordance with a recent survey conducted in UK. 20 A gross over-usage of non-prescription antibiotics, that too not taken for a full course, by most of the patients of URTI was found recently. The study has shown that lack of awareness in the patients could increase the drug resistance problem and awareness about the branded drugs being costlier than the generic drugs was also not there.…”
Section: Discussionmentioning
confidence: 99%
“…This is alongside a tailored approach to provision of medicine information (written, verbal or combined) to particular groups of customers requesting codeine (Hamrosi, Raynor et al 2013;Hamrosi, Raynor et al 2014). In this context the community pharmacy is a trusted source of consumer advice and information around safe and appropriate use of medicines (Wazaify, Shields et al 2005;French and James 2008) and would need to play a central role in information giving to users at point of dispensing.…”
Section: Discussionmentioning
confidence: 99%